Addressing Gaps in Science Competencies: Incorporating Science Communication into Existing Classes - Amy J. Hawkins; Melissa Rowland-Goldsmith; Nicole C. Woitowich (Journal of the Assembly for Expanded Perspectives on Learning, 2023)
Regardless of which career path a scientist decides to take, they must be able to communicate effectively with broad audiences. As such, science communication training has become an essential component of STEM professional development. While multiple national scientific societies have articulated the need to address these skills as in fundamental training, few undergraduate scientific training programs have formally addressed this in their degree programs. Here we present an innovative approach to teach this skill set by blending an online science communication course with existing curricula in the biomedical sciences. Online content from the American Society for Biochemistry and Molecular Biology (ASBMB) Art of Science Communication (ASC) course was integrated into an undergraduate setting. This new iteration utilized components from the successful online course format blended with an institutional course to foster science communication skills. We provide key insights into blended-course development and its impact on learners’ professional development and science communication skills. We contextualize our approach with what others have learned from blended courses and online professional development opportunities for STEM students.